LECTURERS’ READINESS AND INTENTIONS FOR AI INTEGRATION IN INDONESIAN AND INDIAN ELL CLASSROOM - Adi Priantini, Ni Wayan; Alit Riska Dewi, Dewa Ayu; Putri Maharani, Anak Agung; Budiarta, I Komang; Dian Sawitri, Ni Luh Putu; Kumar Negi, Harvinder (English Review: Journal of English Education, 2024)
Investigating the readiness and intention of the lecturers for the use of artificial intelligence (AI) in English language learning is the goal of this study. The questionnaire, online interview, and focus group discussion were all used in the this mixed-methods designed research to collect data. Finding out the lecturers’ readiness  and their intentions on the use of AI applications into their English classrooms are the main points of emphasis. There were 29 English Department lecturers were involved, 11 lecturers from Indonesia (5 males and 6 females) and 18 lecturers from India (6 males and 12 females). It was identified that the lecturers have high readiness in infusing AI into the English language learning classroom. Their readiness was supported by the identified efforts that the lecturers had performed.  Then, it was also figured out that the lecturers have positive intention to infuse AI into their English class.